Alterations in the functional anatomy of working memory in adult attention deficit hyperactivity disorder. - Schweitzer, Julie B.; Faber, Tracy L.; Grafton, Scott T. (American Journal of Psychiatry, 2000)
|WbObjective:[|WB] The authors used a functional neuroimaging study with a working memory probe to investigate the pathophysiology of attention deficit hyperactivity disorder (ADHD). Their goal was to compare regional cerebral blood flow (rCBF) changes related to working memory in adults with and without ADHD. |WbMethod:[|WB] Using {15O}H2O positron emission tomography (PET) studies, the authors compared the sites of neural activation related to working memory in six adult men diagnosed with ADHD and six healthy men without ADHD who were matched in age and general intelligence. |WbResults:[|WB] Task-related changes in rCBF in the men without ADHD were more prominent in the frontal and temporal regions, but rCBF changes in men with ADHD were more widespread and primarily located in the occipital regions. |WbConclusions:[|WB] These data suggest the use of compensatory mental and neural strategies by subjects with ADHD in response to a disrupted ability to inhibit attention to non relevant stimuli and the use of internalized speech to guide behavior. Reprinted by permission of the publisher.